2005
DOI: 10.1037/0021-9010.90.5.980
|View full text |Cite
|
Sign up to set email alerts
|

Turnover Intentions and Voluntary Turnover: The Moderating Roles of Self-Monitoring, Locus of Control, Proactive Personality, and Risk Aversion.

Abstract: This article explores moderators of the relationship between turnover intentions and turnover behavior to better explain why some employees translate intentions into behavior and other employees do not. Individual differences in self-monitoring, locus of control, proactive personality, and risk aversion were examined. Results indicate that self-monitoring and risk aversion moderate the intentions-turnover link. Specifically, the relationship between turnover intentions and turnover is stronger for low self-mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
269
4
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(286 citation statements)
references
References 52 publications
8
269
4
5
Order By: Relevance
“…A recent resurgence of interest in individual differences and how they impact organizational behaviour has focused its attention on proactive personality in addition to the Big Five (Allen, Weeks, & Moffi tt, 2005;Aspinwall & Taylor, 1997;Chan, 2006;Crant, 1995;Erdogan & Bauer, 2005;Fay & Frese, 2001;Kirkman & Rosen, 1999;Parker & Sprigg, 1999;Seibert, Crant, & Kraimer, 1999;Seibert, Kraimer, & Crant, 2001;Thompson, 2005). However, with the exception of Crant (1995) and Thompson (2005), there have been no empirical studies focusing on performance.…”
Section: Proactive Personalitymentioning
confidence: 99%
“…A recent resurgence of interest in individual differences and how they impact organizational behaviour has focused its attention on proactive personality in addition to the Big Five (Allen, Weeks, & Moffi tt, 2005;Aspinwall & Taylor, 1997;Chan, 2006;Crant, 1995;Erdogan & Bauer, 2005;Fay & Frese, 2001;Kirkman & Rosen, 1999;Parker & Sprigg, 1999;Seibert, Crant, & Kraimer, 1999;Seibert, Kraimer, & Crant, 2001;Thompson, 2005). However, with the exception of Crant (1995) and Thompson (2005), there have been no empirical studies focusing on performance.…”
Section: Proactive Personalitymentioning
confidence: 99%
“…Allen, Weeks, and Moffitt (2005) found that locus of control moderated the relation between turnover intentions and voluntary turnover, in that internals with higher intention exhibited more voluntary turnover behavior. Similarly, Chiu, Chien, Lin, and Hsiao (2005) reported that locus of control moderated the relation between job stress and turnover intentions of hospital employees.…”
Section: Locus Of Control In Industrial/organizational Psychologymentioning
confidence: 99%
“…From the above analysis, it can be seen that the mechanism of turnover intention to change into the turnover behavior needs more attentions [4,9]. Affect both conversion relationship between vacancies still exist and influence factors have not been systematically combing, influence mechanism also did not clarify, why people continue to stay in the organization [10,11] is a new research hotspot, and now some theoretical model has not been able to very good interpretation of the enmesh phenomenon, and with in-depth interviews and analysis of the literature, enmesh the concept further highlight, we believe that enmesh may be a new paradigm for turnover and retention research.…”
Section: Problems and A Review Of The Literaturementioning
confidence: 99%
“…Want to leave but can not do, the negative effect of the individual and the organization is greater than the turnover behavior itself [1]. In view of the problem that why evidence shows that turnover intention is the best redictor of the turnover behavior [2,3] but many people who intend to resign did not act [4,5] we conducted a literature analysis. Allen, Weeks, & Moffitt (2005) explained why some people turn their turnover intention into action, and some of them don't.…”
Section: Problems and A Review Of The Literaturementioning
confidence: 99%